Corporate environmental responsibility in Malaysia and India: a preliminary analysis - Ibrahim, Irini; Khor, Poy Hua; Omoola, Sodiq (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRA Malaysia., 2019)
Following the activities of a tyre recycling company in Johor, Malaysia, over 2000 people fell sick and 111 schools were shut when toxic substances were released into the Sungai Kim Kim, a river in Pasir Gudang. This paper examines the relevance of corporate environmental responsibility (CER) policy framework in ensuring constant environmental sustainability by corporate bodies in Malaysia. The paper adopts a comparative law research methodology to assess the potential impact of environmentally sustainable corporate social responsibility across two jurisdictions i.e., Malaysia and India. Looking at existing CER framework in another jurisdiction, the paper argues that voluntary and mandatory CER can strengthen existing environmental regulations in Malaysia under the environmental regulation in Malaysia.